ON THE MULTI-LEVEL CHARACTER OF CRIME - D. A. Shestakov (Russian Journal of Economics and Law)
From the point of view of multi-level approach the modern world crime is viewed , and its 7 types are specified; the main social reasons of crime are marked, the attempts of the Russian criminologists and legislators to form a special criminological legislation for crime prevention are estimated.